USERS' PERCEPTION REGARDING SCIENTIFIC PRODUCTION IN THE FACULTY OF MEDICAL SCIENCES - Daher , Jorge Nader; Panunzio, Amelia Patricia; Navarro, Marlene Hernández (International Journal of Research -GRANTHAALAYAH, 2020)
Higher Education Institutions in all regions must submit to internal and external evaluations carried out with transparency, carried out by independent experts. In the CEAACES evaluation model, research is included as one of the most important processes within university management. An evaluation was carried out at the University of Guayaquil in 2013, being evaluated in category “D”. The scientific production of the FCM was 2%, it ranked last in all the criteria, and it did not meet the requirements for accreditation, due to the tiny percentage that was maintained. Users' perception regarding scientific production is very important for the faculty of medical sciences.